Sosialisasi dan Pelatihan Implementasi Akad-Akad dan Produk Perbankan Syariah - Ivan Rahmat Santoso (Jurnal Pengabdian Pada Masyarakat, 2018)
DISSEMINATION AND IMPLEMENTATION TRAINING OF CONTRACTS AND ISLAMIC BANKING PRODUCTS. The aim of this community service program is to improve comprehensive and integrative understanding of the community, religious leaders and students regarding products/contracts in Islamic banking. It is expected that the training provided by the dedication objects will be able to implement Islamic banking products / contracts in Islamic economic life. Increasing the effectiveness of sharia banking socialization is very important, for that it requires real efforts. To achieve a goal that is desired, it is necessary to make improvements in socializing Islamic banking in the community, it can be seen from what factors are a problem in increasing the effectiveness of sharia banking dissemination in the community, especially in the community. The results of the activities are the community, religious leaders and students who have knowledge of Islamic banking products and contracts and are able to implement in an Islamic economic life.